2021
DOI: 10.1016/j.xcrm.2021.100280
|View full text |Cite
|
Sign up to set email alerts
|

Modifying gut integrity and microbiome in children with severe acute malnutrition using legume-based feeds (MIMBLE): A pilot trial

Abstract: Highlights d Inpatient feeding with standard or legume-based feeds resulted in similar weight gain d Legume feeds limited antibiotic-mediated decrease in gut microbiota richness at day 7 d Microbial fermentation was preserved, which has implications for gut health and integrity d Further testing of legume-enriched feeds in severe acute malnutrition is warranted

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 70 publications
1
34
0
1
Order By: Relevance
“…A case-control study in Mali compared the feces from 143 malnourished children against 110 healthy children, revealing that M. smithii, was significantly downregulated in stool samples from SAM children even after the administration of therapeutic diet (Camara et al, 2021). An additional Ugandan study reported that dying SAM children had a poor gut microbiota diversity, with a significant presence of Proteobacteria and Enterobacteriaceae, and reduction in the SCFAs-producing Bacteroidetes and Firmicutes, and importantly, the marker of gut inflammation fecal calprotectin was upregulated in these children (Calder et al, 2021). Both inflammation in SAM and intestinal function are regulated by SCFAs.…”
Section: Mouse Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…A case-control study in Mali compared the feces from 143 malnourished children against 110 healthy children, revealing that M. smithii, was significantly downregulated in stool samples from SAM children even after the administration of therapeutic diet (Camara et al, 2021). An additional Ugandan study reported that dying SAM children had a poor gut microbiota diversity, with a significant presence of Proteobacteria and Enterobacteriaceae, and reduction in the SCFAs-producing Bacteroidetes and Firmicutes, and importantly, the marker of gut inflammation fecal calprotectin was upregulated in these children (Calder et al, 2021). Both inflammation in SAM and intestinal function are regulated by SCFAs.…”
Section: Mouse Modelmentioning
confidence: 99%
“…Both inflammation in SAM and intestinal function are regulated by SCFAs. Starch and dietary fiber, both of which are not digested in the upper gastrointestinal tract, are anaerobically fermented mainly through glycolysis by resident microbiota in the gut, generating SCFAs (Parada Venegas et al, 2019;Calder et al, 2021). Indeed, SCFAs such as butyrate, acetate and propionate, are secondary products released as by-products of fermentation by healthy microbiota, microorganisms including Lactobacillus reuteri, Faecalibacterium prausnitzii, Bifidobacterium longum, Akkermansia muciniphila, Roseburia spp., and Clostridium cluster XIVa species (Morrison and Preston, 2016;Yan et al, 2016), and among other roles, they improve energy yield, maintain the mucosal integrity in the gut, regulate the colonic pH, prevent the accumulation of potentially pathogenic organisms, and produce vitamins (Calder et al, 2021).…”
Section: Mouse Modelmentioning
confidence: 99%
See 3 more Smart Citations